Folk Art as the Precondition for Developing - Kudinovienė, Jolita; Simanavičius, Aurimas (Pedagogika, 2015)
Folk art is part of ethnic culture consisting of cultural heritage and living traditions and reflects the experience which has been accumulated by most people of the nation since the ancient times. The present-day transfer of values of traditional ethnos from generation to generation depends on the succession of education, customs and traditions, hence, the significance of ethno-cultural education for the preservation of national identity is emphasized in the General Programmes for Secondary Education. The youth’s negative attitude to upholding ethno-culture, their treatment of folk art as a “relic” determined the goal the research – to review the 11th–12th formers’ cognition of folk art as the precondition for the development of ethnic culture. The paper presents the data of the survey which included the 11th and 12th formers (N = 534) of fourteen general education schools in Lithuania and reveals the learners’ attitude to folk art. The interview with teachers of art (N = 25) demonstrated that they identify the cognition of folk art with ethnic art, and notice a lack of attention for this topic in the programmes of art education.